Data: the field where democracy is played - Rincón, Omar (2016)
The War of the data exists. The war, meanwhile, is overcome by the capital, companies and governments. Jobs-Zuckerberg-Page-Bezos-USA and all governments are near total control of data on individuals and society. They chase and find us thanks to our own connected intimacies. The worst thing is we seem happy in hands of surveillance and control. In this context, the data are the field where democracy is played. This text-essay goes from the technological optimism (the big data is only a technology and a wonder that conquers all), to the irony of technology as a power device and, finally, the cynicism of big data as an ideology.